Bionomic and genetic characterization of Anopheles gambiae from Ghana - Kaiser, Maria (My University, 2015)
Abstract Malaria vector control relies principally on the use of insecticides. However, the increasing incidence of insecticide resistance threatens to undermine the effectiveness of this approach, necessitating resistance management strategies. Multiple insecticide resistance is becoming common in West Africa including Ghana. In particular, a population of the major malaria vector Anopheles gambiae, from the Ahafo region of Ghana, shows resistance to all classes of insecticide currently available for use in public health. Insecticide resistance is a primary adaptive characteristic of epidemiological importance although other adaptive traits such as staggered larval time-to-hatch may also be important. Typically, An. gambiae oviposits in small, temporary, sun-lit water bodies and eggs generally hatch 2-3 days post-oviposition. However, staggered distribution of hatching has previously been shown and was also observed in a newly colonized strain (GAH) from Ahafo. The broad aims of this project were therefore to assess and characterize multiple insecticide resistance in An. gambiae from Ahafo as well as to quantify and describe staggered time-to-hatch in a laboratory colony of this population in terms of its adaptive significance and pleiotropic effects on resistance.
Keywords: Anopheles; Malaria